2017
DOI: 10.5380/rber.v6i4.49073
|View full text |Cite
|
Sign up to set email alerts
|

Produção de etanol de segunda geração a partir de caroço de abacate (Persea americana Mill.)

Abstract: . RESUMOO amido é um dos polímeros de glicose mais abundantes no reino vegetal podendo ser utilizado como complemento ou alternativa em substituição à cana-de-açúcar como açúcar fermentável. Atualmente tem se evidenciado a necessidade de novas matrizes de fontes renováveis para a produção de etanol. Como a semente de abacate possui cerca de 20% de amido em sua composição é possível realizar a hidrólise e consequentemente, a fermentação alcoólica. O presente trabalho estudou os processos de hidrólise enzimática… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
1
3
0
3
Order By: Relevance
“…The characterization of avocado seed reported in this study and by different researchers Kowalski et al (2017). reported a starch yield of 20.10% with a difference of 9.69 % from te present study[71].Correa et al (2019) reported a starch yield of 6.85% which differs by 22. 94 % with the resent study [72].…”
supporting
confidence: 45%
“…The characterization of avocado seed reported in this study and by different researchers Kowalski et al (2017). reported a starch yield of 20.10% with a difference of 9.69 % from te present study[71].Correa et al (2019) reported a starch yield of 6.85% which differs by 22. 94 % with the resent study [72].…”
supporting
confidence: 45%
“…Despite a significant 17.9% loss in cellulose content, enzymatic hydrolysis was successful in converting about 87% of the sugars and the fermentation consumed 81% of the hydrolyzed matter, resulting in 22.34 g TRS per 100 g of coconut fiber. Kowalski et al (2017) studied enzymatic hydrolysis processes in avocado seeds to produce second generation ethanol. The ethanol obtained was characterized and the results showed that the raw material used is excellent for biofuel production, with 1.0579 g/L of starch producing 44 L of ethanol per ton of seed, 33.8% of yield ethanol.…”
Section: Cellulose Sources For Ethanol Productionmentioning
confidence: 99%
“…Em diversos países, é consumido na forma de espaguetes, saladas, guacamole, pizza, tortas, além de sopas, maionese, molhos e pastas. Na área industrial, o abacate é matéria-prima para a extração de azeite e etanol, visando à produção de biocombustível de primeira ou segunda geração e fabricação de tintas (Daiuto et al, 2014;Oliveira & Santos, 2016;Kowalski et al, 2017).…”
Section: Introductionunclassified